1996
DOI: 10.1038/bjc.1996.30
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlation of breast tissue parameters using magnetic resonance and X-ray mammography

Abstract: Summary Previous investigators have shown that there is a strong association between the fraction of fibroglandular tissue within the breast as determined by X-ray mammography (per cent density) and breast cancer risk. In this study, the quantitative correlation between per cent density and two objective magnetic resonance (MR) parameters of breast tissue, relative water content and mean T2 relaxation time, as investigated for 42 asymptomatic subjects. Using newly developed, rapid techniques MR measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 28 publications
6
71
0
Order By: Relevance
“…Although water associated absorption correlates with fibroglandular tissue (32,33), contributions from oxyhemoglobin are expected in less proliferating dense tissue (31). Increasing values of t 4 suggest some contributions from water as well as oxyhemoglobin (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although water associated absorption correlates with fibroglandular tissue (32,33), contributions from oxyhemoglobin are expected in less proliferating dense tissue (31). Increasing values of t 4 suggest some contributions from water as well as oxyhemoglobin (23).…”
Section: Discussionmentioning
confidence: 99%
“…TiBS score t 2 was also inversely associated with the dense area of the breast among premenopausal women only. Decreasing values of t 3 suggest a higher water content, which correlates with higher-density tissue (32,33), as well as greater contributions from deoxyhemoglobin (that is, lower oxygen saturation) due to increased cellular proliferation and metabolism in denser tissue (28,31). Decreasing values of t 2 indicate greater deoxyhemoglobin and oxyhemoglobin absorption (that is, total hemoglobin content) as a result of increased tissue vascularization in higherdensity tissue (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so there have been attempts to estimate breast tissue composition by analysis of mammograms 30-37 and MRI data. [5][6][7][8]38 Breast CT is capable of producing high-resolution volumetric images of pendant breasts. 10 Breast CT images are subjectively of higher quality than the images from projection mammography.…”
Section: Ib Breast Tissue Compositionmentioning
confidence: 99%
“…MRI has been used to calculate the water content of a human breast via slices or slabs and with segmentation of 3D images with tailored sequences [24][25][26][27][28][29][30]. It has been shown that percent MRI-density correlates strongly with mammographic PD; however, MRI, as also discussed above for DBT, has been shown to underestimate breast density compared with conventional mammography.…”
Section: Mri Techniquementioning
confidence: 99%